Faktor Yang Berhubungan Dengan Kekurangan Energi Kronis (KEK) Pada Ibu Hamil Di PMB Nurhasanah S.ST Teluk Betung Kota Bandar Lampung - nirma lidia sari (Universitas Mitra Indonesia, 2022)
One of the causes of maternal death is chronic energy deficiency (CED). Pregnant women with CED will bring negative impact for maternal and neonatal health. The purpose of this study was to determine the factors associated with CED in pregnant women. The design of this research is analytic with a cross sectional approach. The population in this study were all pregnant women who had their pregnancy checked at the study site at a certain period. The samples taken were pregnant women whose gestational age was in the second and third trimesters (71 people). Data analysis techniques are univariate and bivariate. Based on the results of the study, 39 pregnant women experienced CED, it was known that primiparas experienced CED 27 people (58.7%). The results of the statistical test obtained a p-value of 0.002, this means that there is a relationship between parity and the incidence of CED with the majority of birth spacing 2 years are 19 people (76.5%). The results of statistical tests obtained p-value 0.102, this means that there is no significant relationship between birth spacing and the incidence of CED. Based on age, respondents 20 and 35 years old are more at risk in experiencing CED with the number 45 respondents (63.4%). Statistical test results obtained p-value 0.000 which means that there is a relationship between maternal age and the incidence of CED. in this study, parity and maternal age had a relationship with the incidence of CED, while birth spacing had no relationship with the incidence of CED. In this study due to the many cases of CED, regardless of parity, birth spacing, maternal age, it is better if pregnant women are given explanations, leaflets and descriptions of the dangers of Chronic Energy Deficiency (CED), so that mothers can understand the impact of CED.